Differences Between the Combination of Maternity Pillow Dual Wedge and Prenatal Yoga Compared with Prenatal Yoga on Anxiety Levels Among Third-Trimester Primigravida Women - Latifah, Anik; Dompepen, Rini Geby; setiawandari, setiawandari (EMBRIO: Jurnal Kebidanan, 2026)
Background: Third-trimester primigravida women often experience anxiety due to physical and psychological changes before childbirth. A preliminary survey at Afiyah Clinic, Gedangan, Sidoarjo, found that 30 out of 37 third-trimester primigravida women (81.08%) experienced anxiety. One non-pharmacological intervention that may reduce anxiety is the combination of a Maternity Pillow Dual Wedge and prenatal yoga. Objective: To determine the anxiety levels of third-trimester primigravida women before and after the administration of a Maternity Pillow Dual Wedge combined with prenatal yoga at Afiyah Clinic, Gedangan, Sidoarjo. Methods: This study employed a quasi-experimental design using a Two-Group Pretest–Posttest Control Design. The sample consisted of 30 respondents divided into intervention and control groups, with 15 participants in each group, selected using purposive sampling. Anxiety levels were measured using the PRAQ-R2 questionnaire. Data were analyzed using the Paired Sample T-Test and Independent Sample T-Test. Results: The Paired Sample T-Test showed a p-value of 0.000, indicating that the combination of a Maternity Pillow Dual Wedge and prenatal yoga significantly reduced anxiety levels among third-trimester primigravida women. The Independent Sample T-Test yielded a p-value of 0.457, indicating no significant difference between the intervention and control groups. Conclusion: The combination of a Maternity Pillow Dual Wedge and prenatal yoga was effective in reducing anxiety among third-trimester primigravida women and has the potential to be applied as a non-pharmacological intervention in midwifery care. Keywords: Anxiety, Maternity Pillow Dual Wedge, Prenatal Yoga, Third-Trimester Primigravida.